The influence of prior cycling on biomechanical and cardiorespiratory response profiles during running in triathletes - Hue, O.; LeGallais, D.; Chollet, D.; Boussana, A.; Prefaut, Ch. (European Journal of Applied Physiology, 1997)
the first minutes of the run segment after cycling in an experimental triathlon were specific in terms of VO2 (oxygen uptake) and cardiorespiratory variables, and nonspecific in terms of biomechanical variables.